Assisted death in eating disorders: a systematic review of cases and clinical rationales - Roff, Chelsea; Cook-Cottone, Catherine (Frontiers in Psychiatry, 2024)
Background: Assisted dying for reasons solely related to an eating disorder (ED) has occurred in multiple countries, including those which restrict the practice to individuals with a terminal condition. The aims of this systematic review were to (1) identify all known cases of assisted deaths among patients with EDs and (2) describe the clinical rationales used to grant patients' requests for assisted death.We conducted a systematic search of peer-reviewed studies and publicly available government reports to identify cases of assisted death in patients with EDs. In reports that included qualitative data about the case, clinical rationales were extracted and grouped into domains by qualitative content analysis.We identified 10 peer-reviewed articles and 20 government reports describing at least 60 patients with EDs who underwent assisted dying between 2012 and 2024. Clinical rationales were categorized into three domains: irremediability, terminality, and voluntary request. Reports emphasized that patients with EDs who underwent assisted death had terminal, incurable, and/or untreatable conditions and had adequate decision-making capacity to make a life-ending decision. Most government reports did not include descriptive-enough data to verify psychiatric conditions.The results of our systematic review underscore considerable gaps in the reporting of assisted death in patients with psychiatric conditions, posing substantial concerns about oversight and public safety. In many cases, the clinical rationales that were used to affirm patients with EDs were eligible for assisted death lack validity and do not cohere with empirical understanding.